Pengembangan Lembar Kerja Peserta Didik Berbasis Inkuiri Terbimbing Berbantuan Multimedia untuk Meningkatkan Keterampilan Proses Sains dalam Pembelajaran IPA di Kelas IV - Putri Nuriantisyah; Endang Widi Winarni; Irwan Koto (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to develop student worksheets, describe materials, language, and graphics, describe student responses and find   out the effectiveness of guided inquiry-based worksheets assisted by multimedia in improving science process skills. This type of research is development using the ADDIE model. The research subjects were students of class IV MI Terpadu Mutiara Asyifa Bengkulu City, which consisted of 18 students of class IVA (experimental class) and 18 students of class IVB (control class). Data collection techniques are interviews, documentation, questionnaires, and tests. The data analysis technique uses Aiken's V, Interrater Reliability, student responses, and quantitative analysis using t-test and N- gain. The results of the study found that the validation of material, language, and graphics, as well as student responses to LKPD were very feasible and well used in learning. The results of the t-test showed the value of Sig.(2-tailed) <0.05 so that there was a difference in learning outcomes between the experimental class and the control class. The results of the N- gain test showed that the science process skills in the experimental class had increased by 48% (medium category). So it can be concluded that guided inquiry-based LKPD assisted by multimedia is effective (moderate) to improve science process skills.